Assessing the impact of crop genetic improvement in Sub-Saharan Africa: research context and highlights - Smale, Melinda (International Food Policy Research Institute, 2006)
Genetic improvement of planting material (in a broad sense) is an important component of agricultural growth for nations and regions in the process of economic development. Asia’s Green Revolutions in rice and wheat are perhaps the best-known examples of dramatic agricultural growth associated with crop genetic improvement. Most experts agree that no such seed-based revolution has occurred in Sub-Saharan Africa, despite frequent, though scattered, episodes of success.